Anatomical Repair With Achilles Tendon Allograft Augmentation for Distal Medial Collateral Ligament Ruptures - Roberto Yáñez, Ph.D., M.D.; Anthony Saravia, M.D.; Hector Zamorano, M.D.; Gaston Caracciolo, M.D.; Cristobal Yañez-Rojo, M.D.; Alejandro Neira, M.Sc.; Carlos De la Fuente, Ph.D. (Arthroscopy Techniques)
Several conditions may require medial collateral ligament (MCL) surgery, especially when high physical demands are required. Thus, we described a technique for anatomical repair of distal MCL rupture using a distal anchor and MCL augmentation through Achilles tendon allograft with proximal bone block and interference screw. This procedure fixes an anchor distally at the tibia. Then, the ligament endings are sutured using a continuous simple-type technique. Subsequently, a low-radiated Achilles tendon allograft is attached proximally and fixed through an interference screw. Finally, the allograft is sutured using a continuous simple-type technique. Our anatomical MCL repair and augmentation allows a reinforced anatomical technique to control the valgus instability caused by MCL distal ruptures, considering the MCL axial traction and posterior oblique ligament fiber orientations.